Frequency of the Palmaris Longus muscle in the Population of Islamabad, Pakistan - Tatheer Zahra; Safura Awais Sumra; Saeed Shafi; Areeba Amjad; Nisma Khan; Ayesha Saif; Namira Khan Khakwani (University of Lahore, 2022)
Abstract Background: The Palmaris Longus is a variable muscle with differing frequencies of presence in different ethnicities, populations and regions. Our study is a cross-sectional study measuring the frequency of the muscle in our sample size in Islamabad. Our aim is to determine the frequency of the palmaris longus muscle in the population of Islamabad, Pakistan. Absence of the palmaris longus does not result in any functional disability. Our objective is to improve our knowledge and spread awareness of the variability of the palmaris longus muscle and its use as a graft tissue at other sites of injury.  Methodology: The presence of the palmaris longus was determined using 4 tests involving various hand movements. Observation of the tendon of the palmaris longus at the wrist confirmed its presence. A sample of 389 participants from the residents of Islamabad was picked randomly. This study was conducted in 2019 at Shifa College of Medicine (Shifa Tameer e Millat University).  Results: Absence of palmaris longus in males and females was 4.7% and 6% respectively. Bilateral absence was seen only in 1% of the study population. Unilateral absence in the right and left hands were seen to be 1.3% and 3.3% respectively. In ambidextrous persons, palmaris longus was present in both hands. In right and left-handed persons, 4.80% and 19.2% of the study population exhibited palmaris longus absence, correspondingly. Conclusion: Overall, the palmaris longus was absent in 5.7% of the entire sample. Further studies can be conducted to establish a relationship between the presence of the palmaris longus muscle and different determinants such as ethnicity and hand dominance etc